APLIKASI PUPUK HIJAU Mucuna bracteataPADA BEBERAPA JENIS MEDIA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.)DI MAIN-NURSERY - ramadhani, Dewi suci; ', Sampoerno '; ', Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research to determine combination of green fertilizer Mucuna bracteata in some type of soil media and single-factor as well getting the best dose to the growth of oil palm seedlings. This reseach uses three type of  soil media namely, sub soil Ultisol taken from desa batu belah, kab.kampar, province Riau, sub soil Inceptisol taken from Faculty of Agriculture, University of Riau and peat soil taken from Desa Rimbo Panjang, Kab. Kampar, Province Riau  as growing media.Three type of media is utilized as soil media treatment of soil mix for growing oil palm seed is ground Ultisol sub soil mixed with peat soil and sub soil Inceptisolmixed with peat soil. Treatment of the soil media mix with appropriate comparison would be able to increase the growth of oil palm seedlings that can be developed with green fertilizer Mucuna bracteata appropriate and in accordance with the ability of the soil. This research exprimental  units were arranged in Factorial Competely  Randomized Design with three replication. The first factor is composed of green fertilizer mucuna bracteata P0: Green fertilizer mucuna dose 0 g/polybag, P1: Green fertilizer mucuna dose 10,9 g/polybag, P2: Green fertilizer mucuna dose 21,6 g/polybag, P3: Green fertilizer mucuna dose 32,4 g/polybag. The second factor comprises several type of soil medium consisting of T1: Sub soil Ultisol + Peat soil, T2: Sub soil Inceptisol + Peat soil. Parameters studiet were an increase plant height, leaf number increase, the increase in diameter stump, root volume, root canopy ratio, dry weight and visual rupture leaves. The results showed that administration  of mucuna green fertilizer 21.6 g/polybag on the type of media subsoil  Inceptisol +  peat soil gives the best growth to the growth of oil palm seedlings. It is the same with the standards recommended by the research center of Indonesia oil palm seedlings. Keywords :palm oil, Mucuna bracteata, type of soil